The Role of Law in Governing Fintech Innovation and Risk Management - Hasnah Aziz; Ibrahim Aji; Mahfudlon; Harry Sudhana; Adi Saputra (Cita Konsultindo Research Center, 2026)
This study examines the role of law in governing financial technology (fintech) innovation while ensuring effective risk management in rapidly evolving digital financial ecosystems. As fintech disrupts traditional financial services through technologies such as blockchain, artificial intelligence, and digital payments, regulatory frameworks face increasing pressure to balance innovation with consumer protection and systemic stability. This paper analyzes how legal systems respond to fintech developments by exploring regulatory approaches, including principles-based regulation, regulatory sandboxes, and cross-border legal harmonization. It highlights key risks associated with fintech, such as data privacy concerns, cybersecurity threats, financial fraud, and regulatory arbitrage, and evaluates how legal instruments mitigate these challenges. Furthermore, the study discusses the role of law in fostering trust, promoting responsible innovation, and ensuring financial inclusion. Using a qualitative approach, the research draws on comparative legal analysis and recent policy developments across emerging and developed markets. The findings suggest that adaptive, flexible, and technology-neutral legal frameworks are essential to support innovation while maintaining financial stability and public confidence. Ultimately, the paper underscores the importance of dynamic legal governance in shaping a sustainable and resilient fintech ecosystem.